Environmental knowledge learned from the park - Mack John, speaker; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
With continued and increasing human development or alteration of natural environments and ecosystems, parks and protected areas have become increasingly valuable as natural areas, not only for public enjoyment and experiences, but also as important, dynamic laboratories for demonstrating international, regional, and local connections and the importance of stewardship across or without boundaries. From an international perspective, I will discuss how a preliminary migratory bird research project may broaden our perspective of how vastly distant and different habitats are important to species. From a regional perspective, air quality issues can not only protect park habitats but I will illustrate how other industries are attempting to contribute to solutions. On a landscape scale, Rocky Mountain National Park's elk and vegetation management plan is an example of implementing habitat restoration and being a springboard for multi-agency collaboration of habitat use, wildlife disease study, and management of elk that is important to local economies.
Environmental knowledge learned from the park – can parks and protected areas provide opportunities for landscape scale education and collaboration?
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Presented during Plenary Session II.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses